Voyage of the Jaffa Wind - Abbott, Tony.; Merrell, David (New York : Scholastic, 2002)
Eric and his friends sail aboard the "Jaffa Wind" to rescue Max, who has been mysteriously kidnapped.
"A Little Apple paperback."
5.2
3-6
Keywords: Missing children -- Fiction; Magic -- Fiction; Voyages and travels -- Fiction; Fantasy; Missing children -- Fiction; Magic -- Fiction; Voyages and travels -- Fiction; Fantasy fiction